The rural poverty trap: which way out for South Africa? - Matunhu, Jephias (Tamara, 2016)
Revolutionary movements in South Africa and elsewhere in the world were founded on the need to remove political systems that were considered as the root cause of poverty and suppression. Today, South Africa is a sovereign state and poverty remains. As much as poverty was part of the Liberation Movement agenda, it may be considered as a trap in South Africa where the gap between the rich and the poor remains very wide. The xenophobic attacks in May 2008 have been attributed to poverty. The discourse of rural development centres on fighting rural poverty. However, there is no commonly shared definition of both rural development and rural poverty. To further complicate the discourse, there is no consensus on how to measure both phenomena. Fighting rural poverty demands wisdom for it involves the commitment of scarce economic and non economic resources in an environment that is beset with class struggle. The question is- which way out of the poverty trap? The paper recommends agro-based solutions among other measures.